Microbiological analysis of ground beef sold at butchers in markets of Itapetinga – BA (Research, Society and Development, 2020)
The present work aimed to analyze the microbiological characteristics of beef before and after grinding process in butchers of the city of Itapetinga-Ba. Three samples from two different butchers were evaluated before and after grinding to quantify fecal coliforms, Staphylococci and Salmonellas spp. The results obtained were compared with current legislation and classified as own or improper for consumption. For the results of thermotolerant coliforms butcher I and II presented contamination for ground meat, only samples A1 and A2 of butcher I, in pieces, are in good sanitary condition and sample B3 (ground meat) of butcher II. Regarding the presence of Staphylococci, samples A1 and B3 meat (Pieces) and A1, B1, B2, B3 meat (Ground) are above the tolerable limit by current legislation. Salmonella spp was found in all samples analyzed. Given this, it is concluded that the samples studied presented contamination levels by at least one type of microorganism, above the tolerable by the National Health Surveillance Agency, making it improper for consumption.